Ultrasound-Guided Pudendal Nerve Block Combined with Propofol Deep Sedation versus Spinal Anesthesia for Hemorrhoidectomy: A Prospective Randomized Study - Jian He; Lei Zhang; Dong L. Li; Wan Y. He; Qing M. Xiong; Xue Q. Zheng; Mei J. Liao; Han B. Wang (Pain Research and Management)
Background and Objectives. Several anesthesia techniques were applied to hemorrhoidectomy, but postoperative pain and urinary retention were still two unsolved problems. The aim of this prospective randomized study was to evaluate the effect of ultrasound-guided pudendal nerve block (PNB) combined with deep sedation compared to spinal anesthesia for hemorrhoidectomy. Methods. One hundred and twenty patients undergoing Milligan–Morgan hemorrhoidectomy were randomized to receive PNB combined with deep sedation using propofol (Group PNB, n = 60) or spinal anesthesia (Group SA, n = 60). Pain intensity was assessed using the visual analogue scale (0: no pain to 10: worst possible pain). The primary outcome was pain scores recorded at rest at 3, 6, 12, 24, 36, and 48 h and on walking at 12, 24, 36, and 48 h postoperatively. Secondary outcomes were analgesic consumption, side effects, and patient satisfaction after surgery. Results. Ultrasound-guided bilateral PNB combined with deep sedation using propofol could successfully be applied to Milligan–Morgan hemorrhoidectomy. Postoperative pain intensity was significantly lower in Group PNB compared to Group SA at rest at 3, 6, 12, 24, 36, and 48 h (p<0.001) and during mobilization at 12, 24, 36, and 48 h (p<0.001) postoperatively. Sufentanil consumption in Group PNB was significantly lower than that in Group SA, during 0–24 h (p<0.001) and during 24–48 h (p<0.001) postoperatively. Urinary retention was significantly lower in Group PNB compared to Group SA (6.9% vs 20%, p=0.034). The patients in Group PNB had higher satisfaction compared to Group SA (p<0.001). Conclusions. Ultrasound-guided PNB combined with propofol sedation is an effective anesthesia technique for Milligan–Morgan hemorrhoidectomy.